Synthesis, X-ray Crystal Structure and Theoretical Calculations of Antileishmanial Neolignan Analogues - do Nascimento, Josenaide P.; Santos, Lourivaldo S.; Santos, Regina Helena A.; Tozzo, Erica; Ferreira, Janaina G.; do Carmo, Maria Carolina L.; Brasil, Davi S. B.; Alves, Claudio N. (Soc Brasileira Quimica, 2010)
The synthesis and X-ray crystal diffraction structure of two analogues of neolignans, 2-(4-chlorophenyl)-1-phenylethanone (20) and 2-[(4-chlorophenyl)thio]-1-(3,4-dimethoxyphenyl)propan-1-one (12) is described. The compound 12 presents activity against intracellular Leishmania donovani and Leishmania amazonensis amastigotes that cause cutaneous and visceral leishmaniasis. In addition, the density functional theory (DFT) with the B3LYP hybrid functional was employed to calculate a set of molecular descriptors for nineteen synthetic analogues of neolignans with antileishmanial activities. Afterwards, the stepwise discriminant analysis was performed to investigate possible relationship between the molecular descriptors and biological activities. Through this analysis the compounds were classified into two groups active and inactive according to their degree of biological activities, and the more important properties were charges on some key atoms, electronic affinity and ClogP.
Keywords: neolignans; antileishmanial; B3LYP; X-ray crystal structure